KEMISKINAN DAN PEMBERDAYAAN EKONOMI DALAM PERSPEKTIF AL-QUR’AN: STUDI QUR’AN TEMATIK DENGAN PENDEKATAN GROUNDED THEORY - Dani Abdu Latief; Muhammad Alif (Adisam Publisher, 2025)
Poverty is a social issue that receives significant attention in Islamic teachings, particularly in the Qur'an. Islam not only acknowledges poverty as a societal reality but also offers normative solutions to address it through both spiritual and structural approaches. This study explores the Qur'anic perspective on poverty and its proposed strategies for empowering the community's economy. Employing a qualitative method through library research, the study thematically analyzes verses that discuss poverty and economic tools such as zakat, infaq, alms, and the prohibition of usury. The findings indicate that the Qur'an considers poverty a condition that must be eliminated using equitable social and economic instruments, while also highlighting the communal obligation to achieve collective welfare. From the Qur'anic viewpoint, economic empowerment encompasses not just material aspects but also spiritual ones, emphasizing a strong work ethic, fair distribution of wealth, and social solidarity.